2022
DOI: 10.3389/fragi.2022.1007098
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in epigenetic age in Mediterranean high longevity regions

Abstract: Sex differences in aging manifest in disparities in disease prevalence, physical health, and lifespan, where women tend to have greater longevity relative to men. However, in the Mediterranean Blue Zones of Sardinia (Italy) and Ikaria (Greece) are regions of centenarian abundance, male-female centenarian ratios are approximately one, diverging from the typical trend and making these useful regions in which to study sex differences of the oldest old. Additionally, these regions can be investigated as examples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 112 publications
2
11
2
Order By: Relevance
“…Contrary to previous work showing men have higher epigenetic aging rates than women (Engelbrecht et al, 2022, Kankaanpää et al, 2022, Horvath et al, 2016, we found no significant effect of sex on epigenetic aging. However, this is likely due to the restricted age group used in this study, as all participants were currently attending college.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous work showing men have higher epigenetic aging rates than women (Engelbrecht et al, 2022, Kankaanpää et al, 2022, Horvath et al, 2016, we found no significant effect of sex on epigenetic aging. However, this is likely due to the restricted age group used in this study, as all participants were currently attending college.…”
Section: Discussioncontrasting
confidence: 99%
“…This finding is consistent with previous studies showing that increased alcohol consumption is associated with an increased epigenetic age estimation (Luo et al, 2020, Mills et al, 2019, Rosen et al, 2018); however, a family history of alcohol consumption is not. Contrary to previous work showing men have higher epigenetic aging rates than women (Engelbrecht et al, 2022, Kankaanpää et al, 2022, Horvath et al, 2016), we found no significant effect of sex on epigenetic aging. However, this is likely due to the restricted age group used in this study, as all participants were currently attending college.…”
Section: Discussioncontrasting
confidence: 99%
“…Sex divergent CP structure changes have been described, e.g., in the case of calcifications ( 58 ). In terms of age and CP relationship, women were younger in terms of our sample, but they also tend to be younger in metabolic age ( 59 ), telomere length ( 60 ), and complex differences in metabolism including mitochondrial function ( 61 ). Thus, the negative longitudinal association between CP volume and age in men could be a sign of a ceiling effect: lack in CP increase after a certain volume threshold (which could possibly occur around 77.5–91.4 years of age for men, as is our last quartile).…”
Section: Discussionmentioning
confidence: 83%
“…The present findings provide additional support for the contention that an epigenetic biomarker of prenatal exposure to phthalates may be evident in infants as young as three months of age [76], and indicates that epigenetic markers of biological aging, EAA, in young infants are sensitive to prenatal exposure to DEHP. This may be influenced by sex differences in aging, as men have been found to display positive EAA compared to women, across epigenetic clocks (e.g., Horvath pan-tissue, Horvath skin and blood, Hannum, GrimAge, PhenoAge, and Pace of Aging) [77,78]. Additional investigations examining associations between prenatal phthalate exposures, as well as other environmental chemicals (e.g., metals, air pollutants, pesticides), and epigenetic clocks in very young pediatric samples may provide novel insights into the early molecular programming of disease susceptibility and contribute to the continued evolution of the DOHaD paradigm [79].…”
Section: Discussionmentioning
confidence: 99%